The Effects of Chromium and Nickel on the Passivation Behaviour of Sputter-Deposited W-Cr-Ni Alloys in 12 M HCl Solution - Bhattarai, Jagadesh (Scientific World, 2010)
The passivity of sputter-deposited ternary W-Cr-Ni alloys is investigated by immersion tests and electrochemical measurements in 12 M HCl solution at 30°C, open to air. Particular attention is paid to the effects of alloying elements to the corrosion behavior. All the examined amorphous or/and nanocrystalline W-Cr-Ni alloys are passivated spontaneously even in an aggressive environment of 12 M HCl, and hence these alloys showed higher corrosion resistance than those of alloyconstituting elements. The chromium addition suppresses the anodic dissolution current because of the formation of tetravalent chromium oxyhydroxide having a relatively high activity for both cathodic oxygen and hydrogen reduction with a consequent ennoblement of the open circuit potential. The ennoblement of the open circuit potential leads to the formation of the passive chromium oxyhydroxide film. It is, therefore, considered that the addition of chromium improves synergistically the corrosion resistance and passivating abilities of the sputter-deposited binary W-Ni alloys in 12 M HCl solution. Keywords: Sputter-deposition; Ternary W-Cr-Ni alloys; Corrosion-resistant; Electrochemical measurements. DOI: 10.3126/sw.v7i7.3819 Scientific World Vol.7(7) 2009 pp.24-28